Detecting the stepwise propagation of the Eastern Sicily thrust belt (Italy): insight from thermal and thermochronological constraints. (9th May 2014) - Di Paolo, Lea; Olivetti, Valerio; Corrado, Sveva; Aldega, Luca; Balestrieri, Maria Laura; Maniscalco, Rosanna
Abstract An extensive dataset of vitrinite reflectance, FTIR parameters on organic matter, illite content in mixed layers illite‐smectite, apatite fission tracks and U‐Th/He dating has been used to reconstruct the stepwise propagation of the Eastern Sicily fold‐and‐thrust belt during Late Palaeogene and Neogene times. The results indicate that the fold‐and‐thrust belt is divisible into two levels of thermal maturity. These levels consist of a less evolved level of thermal maturity that records limited sedimentary burial and minor heating, and a more evolved level of thermal maturity that indicates tectonic burial and exhumation at different times. Deformation and exhumation of shallowly buried units are linked to wedge forward propagation by low‐angle thrusts, whereas the evolution of deeply buried units is associated with tectonic imbrications by duplex formation and steep thrusts. The two tectonic styles alternate during evolution of the fold‐and‐thrust belt under low erosion rates.